Development and characterization of highly stable silver nanoparticles as novel potential antimicrobial agents for wound healing hydrogels - Massironi, Alessio (2022)
Recurrent microbial infections are a major cause of surgical failure and morbidity. Wound healing strategies based on hydrogels have been proposed to provide at once a barrier against pathogen microbial colonization, as well as a favorable environment for tissue repair. Nevertheless, most biocompatible hydrogel materials are more bacteriostatic than antimicrobial materials, and lack specific action against pathogens. Silver-loaded polymeric nanocomposites have efficient and selective activity against pathogenic organisms exploitable for wound healing. However, the loading of metallic nanostructures into hydrogels represents a major challenge due to the low stability of metal colloids in aqueous environments. In this context, the aim of the present study was the development of highly stable silver nanoparticles (AgNPs) as novel potential antimicrobial agents for hyaluronic acids hydrogels. Two candidate stabilizing agents obtained from natural and renewable sources, namely cellulose nanocrystals and ulvan polysaccharide, were exploited to ensure high stability of the silver colloid. Both stabilizing agents possess inherent bioactivity and biocompatibility, as well as the ability to stabilize metal nanostructures thanks to their supramolecular structures. Silver nitrate reduction through sodium borohydride in presence of the selected stabilizing agents was adopted as a model strategy to achieve AgNPs with narrow size distribution. Optimized AgNPs stabilized with the two investigated polysaccharides demonstrated high stability in phosphate buffer saline solution and strong antimicrobial activity. Loading of the developed AgNPs into photocrosslinked methacrylated hyaluronic acid hydrogels was also investigated for the first time as an effective strategy to develop novel antimicrobial wound dressing materials.